2023
DOI: 10.1002/ptr.7746
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba extract protects against diabetic cardiomyopathy by restoring autophagy via adenosine monophosphate‐activated protein kinase/mammalian target of the rapamycin pathway modulation

Abstract: Studies demonstrated that Ginkgo biloba extract (GBE) played a cardioprotective role in diabetic conditions. Impaired autophagy is one of the mechanisms underlying diabetic cardiomyopathy (DCM). The effect of GBE on autophagy has been observed in several diseases; however, whether GBE can ameliorate DCM by regulating autophagy remains unclear. Here, we investigated the effect of GBE on DCM and the potential mechanisms regarding autophagy using a streptozotocin (STZ)-induced diabetic rat model and a high-glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…43 Our study results revealed that hyperglycemia upregulated MALAT1 expression and LC3B , an autophagy marker, in both macrophages and diabetic rats after balloon injury of the carotid artery. However, Yang et al 44 reported that impaired autophagy was observed in high glucose-stimulated H9C2 cells and heart tissue from diabetic patients. Analysis of the effect of MALAT1 on different cell types and disease models may help us understand these seemingly contradictory reports on MALAT-mediated activation and inhibition of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…43 Our study results revealed that hyperglycemia upregulated MALAT1 expression and LC3B , an autophagy marker, in both macrophages and diabetic rats after balloon injury of the carotid artery. However, Yang et al 44 reported that impaired autophagy was observed in high glucose-stimulated H9C2 cells and heart tissue from diabetic patients. Analysis of the effect of MALAT1 on different cell types and disease models may help us understand these seemingly contradictory reports on MALAT-mediated activation and inhibition of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgo biloba extract has been shown to regulate the AMPK/mTOR pathway, activate autophagy, and improve cardiac function by decreasing myocardial pathological changes ( Yang et al, 2023 ).…”
Section: Natural Products For Regulating Diabetic Microvascular Compl...mentioning
confidence: 99%